Virus diseases of chickpea - Kumar, P. Lava; Waliyar, Farid; Kumari, S. (2008)
Chickpea (Cicer arietinum L.) is the most important pulse crop and is an important source of dietary protein. It is mainly grown in Indian subcontinent, Ethiopia, Turkey, Mexico, and some regions around the Mediterranean and in the Middle East. Recently the crop is gaining prominence in Canada and Australia. Two types of chickpea are grown commonly, the ‘desi’type in Indian subcontinent and ‘kabuli’ type in West Asia and Mediterranean region, and this type is gaining popularity. Several viruses have been reported to infect chickpea. The most important of them worldwide are Alfalfa mosaic virus, Bean leaf roll virus, Beet western yellows virus, Chickpea chlorotic dwarf virus, Cucumber mosaic virus, Chickpea stunt disease-associated virus and Faba bean necrotic yellows virus. A brief account on virus properties, diagnosis and management of these viruses are presented.